Microwave switch based on waveguide tee for the compression cavity pulse shaper - Бондаренко, И.Н.; Горбенко, Е.А.; Краснощок, В.И. (Radiotekhnika, 2016)
The features of the switch based on a waveguide tee to control the modes of accumulation and emission of energy high-q resonator drive are studied. It is shown that for effective use of microwave switch based on a waveguide tee it is necessary to ensure high accuracy of positioning elements (10...20 µm), the instability of the pump generator – no worse than 10-4, the resonator's quality factor in storage mode – no worse than 104, high conductivity controlled regulatory element and small losses introduced in them in the accumulation mode.